Water and land based rehabilitation for Achilles tendinopathy in an elite female runner - Beneka, A. G.; Malliou, B. C.; Benekas, G. (British Journal of Sports Medicine, 2003)
On initial presentation, the athlete was treated with anti-inflammatory drugs. Although the symptoms decreased, the Achilles tendinopathy was not resolved. Kader et al aintain that Achilles tendinitis is a degenerative, not an inflammatory, condition. Although the present case was an early stage of Achilles tendinopathy, it also was not an inflammatory condition.